The Effect of Corporate Social Responsibility and Financial Performance on Stock Returns in the Palm Oil Industry Listed on the Indonesia Stock Exchange, 2018 to 2024 - Widodo, Muhammad Ari; Arifin, Zaenal (Cita konsultindo, 2026)
This study investigates effect of Corporate Social Responsibility disclosure and financial performance on stock returns of palm oil companies listed on the Indonesia Stock Exchange from 2018 to 2024. Financial performance is measured using Return on Equity and Current Ratio and Debt to Equity Ratio and Total Asset Turnover and Price to Earnings Ratio. The study applies a quantitative associative approach using secondary data obtained from firms’ annual and sustainability reports. Purposive sampling results in 22 firms and an unbalanced panel dataset. Panel data regression is employed using EViews 12. The results indicate Corporate Social Responsibility and financial performance variables do not significantly influence stock returns. However partial analysis shows that Corporate Social Responsibility disclosure has a positive and significant effect on stock returns. In contrast all financial performance indicators show no significant relationship with stock returns. These findings imply that within Indonesian palm oil sector investors respond to social responsibility disclosure more than traditional financial ratios when assessing return prospects.